PENGARUH PELAKSANAAN PROGRAM PEMBERDAYAAN DESA (PPD) TERHADAP KEBERDAYAAN MASYARAKAT DESA DI KABUPATEN KUANTAN SINGINGI - SISPA PEBRIAN; SUARDI TARUMUN; ROSNITA ROSNITA (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
There four purposes of this study are:(1) to analyze the influence of the characteristics of beneficiaries towards their empowerment; (2) to analyze the effect of mentoring programs toward their empowerment; (3) to analyze the institutional organization and management of village government towards their empowerment (4) to analyze the characteristics of the beneficiaries, guidance, organization and management of village official government toward program of village empowerment (Program Pemberdayaan Desa/ PPD).